Investigating the acceptance of shared e-scooters: Empirical evidence from Turkey - Öztaş Karlı, Rukiye Gizem; Karlı, Halil; Celikyay, Hatice Selma; Karlı, Rukiye Gizem Öztaş; Karlı, Halil (Elsevier, 2022)
Shared e-scooters are a newly found type of electric vehicle, emerging from and utilized within micro-mobility systems across the globe. The effectiveness of their performance, however, remains contingent on the number of individuals willing to accept them. This study aims to determine those predictors which influence behavioral intention toward shared e-scooters. The suggested research model is based on the extended Unified Theory of Acceptance and Use of Technology (UTAUT2), along with price sensitivity and environmental awareness. Data was gathered through an online questionnaire of 467 participants in Turkey, from which we obtained 413 valid responses. Model explains the 60% variance in the behavioral intention to use e-scooters. Primary findings demonstrated that behavioral intention is significantly affected by social influence (R2 = .319), effort expectancy (R2 = .194), performance expectancy (R2 = .179), and price sensitivity (R2 = .154). As shared e-scooters are novel to the Turkish mobility system, we analyzed findings to help practitioners and policymakers develop strategies that will enhance interest in adopting shared e-scooters within micro-mobility systems.
Keywords: E -Scooters; Technology Acceptance; Shared Micro-Mobility; Turkey; Adoption; Utaut2